Theranostic inorganic–organic hybrid nanoparticles with a cocktail of chemotherapeutic and cytostatic drugs. Issue 16 (5th April 2023) - Khorenko, Mikhail; Pfeifer, Juliana; Napp, Joanna; Meschkov, Anna; Alves, Frauke; Schepers, Ute; Feldmann, Claus
Abstract : Theranostic inorganic–organic hybrid nanoparticles (IOH-NPs) with a cocktail of chemotherapeutic and cytostatic drugs and outstanding drug loading (71–82% of total nanoparticle mass) are evaluated with different cell lines and tumor spheroids. Abstract : Theranostic inorganic–organic hybrid nanoparticles (IOH-NPs) with a cocktail of chemotherapeutic and cytostatic drugs and a composition Gd2 3+ [(PMX)0.5 (EMP)0.5 ]3 2−, [Gd(OH)] 2+ [(PMX)0.74 (AlPCS4 )0.13 ] 2−, or [Gd(OH)] 2+ [(PMX)0.70 (TPPS4 )0.15 ] 2− (PMX: pemetrexed, EMP: estramustine phosphate, AlPCS4 : aluminum(iii ) chlorido phthalocyanine tetrasulfonate, TPPS4 : tetraphenylporphine sulfonate) are presented for the first time. These IOH-NPs are prepared in water (40–60 nm in size) and have a non-complex composition with outstanding drug loading (71–82% of total nanoparticle mass) of at least two chemotherapeutic or a mixture of cytostatic and photosensitizing agents. All IOH-NPs show red to deep-red emission (650–800 nm) to enable optical imaging. The superior performance of the IOH-NPs with a chemotherapeutic/cytostatic cocktail is validated based on cell-viability assays and angiogenesis studies with human umbilical vein endothelial cells (HUVEC). The synergistic anti-cancer effect of the IOH-NPs with a chemotherapeutic cocktail is shown in a murine breast-cancer cell line (pH8N8) and a human pancreatic cancer cell line (AsPC1), whereas the synergistic cytotoxic and phototoxic efficacy is verified in response to illumination of HeLa-GFP cancer cells, MTT assays with human colon cancer cells (HCT116), and normal human dermal fibroblasts (NHDF). HepG2 spheroids as 3D cell cultures prove the effective uptake of the IOH-NPs with high uniform distribution and the release of the chemotherapeutic drugs with the strong synergistic effect of the cocktail of drugs.